Wavelength-Tunable Kerr-Lens Mode-Locked Femtosecond Cr:ZnS Laser With a ∼300-nm Tuning Range From 2.2 to 2.5 μm - Wang, Qing; Wang, Runyu; Yang, Fan; Li, Yan (Frontiers in Physics, 2022)
Tunable 2 3-μm femtosecond lasers are highly interested in various applications, such as medical diagnostics and molecular spectroscopy. Cr:ZnSe/ZnS are extremely suited for broadband tunable femtosecond lasers due to their excellent emission bands. In this paper, we demonstrate a wavelength-tunable Kerr- lens mode-locked Cr:ZnS laser by utilizing a birefringent filter. The Group Delay Dispersion of the operation and thickness of the birefringent are finely optimized. With the rotation of the birefringent filter, the scheme offers a tuning bandwidth over 300 nm from 2220 nm to 2520 nm. To the best of our knowledge, it is the broadest tuning range in reported femtosecond Cr:ZnS lasers.